An Investigation into Social Intelligence and Job Performance of Teacher Educators - Su Myat Aye; Yin Mar Saw (International Journal of Educational Research & Social Sciences, 2026)
The main purpose of this study was to investigate the impact of teacher educators' social intelligence on their job performance. A quantitative research approach was employed. A total of 1,102 teacher educators from three education universities and nine education degree colleges participated in the study, and a cluster sampling technique was used to select the participants. The findings revealed that the teacher educators' level of social intelligence was above average. The results of the independent-samples t-test indicated that there were no significant differences in social intelligence based on gender or marital status. However, the results of the one-way analysis of variance (ANOVA) showed that younger teacher educators had significantly higher levels of social intelligence than older teacher educators. The findings also indicated that the teacher educators' job performance was satisfactory. The independent-samples t-test revealed that gender was significantly related to job performance, with female teacher educators demonstrating better job performance than their male counterparts. However, no significant differences in job performance were found based on marital status or age. Furthermore, the results of the correlation analysis showed that teacher educators' social intelligence was positively associated with their job performance. Multiple regression analysis further revealed that social intelligence was a significant predictor of teacher educators' job performance, accounting for 8.7% of the variance in job performance.